Language Context of modern science case study compared to linguist theory - Syaiful Umam (Jurnal Studi Islam dan Sosial, 2018)
As long as man stood throughout the ages at every word and thought and thought of the significance of his meaning, intentionally or unintentionally,and since man lives in his social nature,it must be imagined or scrutinized in everything that is said to him. The semantic studies is not new and if some of his terminology is modern and the semantic studies are old but In order contexts,the greeks Indians and another nation have a share of the semantic lesson. In this research, the accuracy of what is meant by this science has been examined and it has stood at the suspicion of some of it and what is seen by some scholars of theology and its difference from the meaning of the word, the context language of the linguistic root (Q and S) and the word source (the meaning refers to language is (revenue). Dr tammam hasan emphasize these linguistic meaning that indicate the sequence or revenue. The meaning of the context, and the seen in two respect, first: Sequeltial element that achive the structure and texture,and the context of this angle is called. And the second: the sequence of event that accompanied the performance of language and was related to communication and in this context is called the context. The term context in the study of modern language of the term is difficult to exact identification. Although it represent a theory of the most semantic and tried to narrow research without redundant useless,but chose what the student can learn from the door of this science and god is the guardian of success.